Atmospheric oxidation of selected chlorinated alkenes by O3, OH, NO3 and Cl. (December 2017) - Zhang, Qun; Chen, Yi; Tong, Shengrui; Ge, Maofa; Shenolikar, Justin; Johnson, Matthew S.; Wang, Yifeng; Tsona, Narcisse T.; Mellouki, Abdelwahid; Du, Lin
Abstract: An experimental study on the 3-chloro-2-methyl-1-propene (CMP), 2, 3-dichloropropene (DCP) and 3, 4-dichlorobutene (DCB) reactions with atmospheric oxidants at (298 ± 1) K and atmospheric pressure is reported. Rate constants for the gas phase reactions of the three chlorinated alkenes with O3, OH and NO3 radicals and Cl atom were determined in a 100 L Teflon reactor by gas chromatography with flame ionization detector (GC-FID). The obtained rate constants are (3.03 ± 0.15) × 10 −18, (3.83 ± 1.30) × 10 −11, (1.99 ± 0.19) × 10 −14, and (2.40 ± 0.41) × 10 −10  cm 3 molecule −1 s −1 for CMP reactions with O3, OH, NO3, and Cl, respectively, (4.62 ± 1.41) × 10 −20, (1.37 ± 1.02) × 10 −11, (1.45 ± 0.15) × 10 −15 and (1.30 ± 0.99) × 10 −11  cm 3 molecule −1 s −1 for DCP reactions and (2.09 ± 0.24) × 10 −19, (1.45 ± 0.59) × 10 −11, (3.00 ± 0.82) × 10 −16 and (1.91 ± 0.19) × 10 −10  cm 3 molecule −1 s −1 for DCB reactions. The CMP reaction products were detected and possible reaction mechanisms of their formation were proposed. Chloroacetone was found to be the major product in all four oxidation reactions. The loss process of CMP in the atmosphere is mostly controlled by its reaction with the OH radical during daytime and with NO3 during nighttime, with lifetimes of 3.6 h and 27.9 h respectively. Atmospheric implications of both these reactions and their potential products are discussed. Highlights: Rate constants of CMP, DCP and DCB reactions with atmospheric oxidants are determined. Possible CMP reaction mechanisms are proposed. The atmospheric lifetime of CMP, DCP and DCB are determined. The atmospheric implications of the CMP reactions are discussed.